2011
DOI: 10.1177/000313481107700523
|View full text |Cite
|
Sign up to set email alerts
|

Operative Intervention for Complete Pancreatic Transection in Children Sustaining Blunt Abdominal Trauma: Revisiting an Organ Salvage Technique

Abstract: Complete pancreatic transection (CPT) in children is managed commonly with distal pancreatectomy (DP). Alternatively, Roux-en-Y distal pancreaticojejunostomy (RYPJ) may be performed to preserve pancreatic tissue. The purpose of this study was to review our experience using either procedure in the management of children sustaining CPT after blunt abdominal trauma. We retrospectively reviewed the records of all children admitted to our institution during the last 15 years who were confirmed at operation to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Pancreatic trauma reportedly accounts for 0.2% of all types of trauma and 5%-7% of abdominal trauma, with trauma-related organ damage being extremely rare [1,2]. Thus, very few detailed reports exist on the long-term outcomes of pancreatic trauma, particularly in terms of functional outcomes, such as endocrine and exocrine function.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic trauma reportedly accounts for 0.2% of all types of trauma and 5%-7% of abdominal trauma, with trauma-related organ damage being extremely rare [1,2]. Thus, very few detailed reports exist on the long-term outcomes of pancreatic trauma, particularly in terms of functional outcomes, such as endocrine and exocrine function.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Letton-Wilson procedure, there is only one case series compared with DP. It was concluded Letton-Wilson procedure seems otherwise equivalent to DP and preserves significant pancreatic glandular tissue and spleen [4]. Although, in recent years, reports have been increasingly supporting NOM for paediatric pancreatic injury [5,6], therapeutic protocols are not yet established.…”
Section: Discussionmentioning
confidence: 99%
“…24 In our opinion, this is the main argument for attempting primary CM in all cases. Indeed, because of the high morbidity rates, even for elective surgery, 14 we consider that surgery should be reserved for hemodynamically instable patients or patients with hollow organ injuries. Even as regards LOS, Wood et al 11 reported that though operative management significantly decreased the rate of pseudocysts it failed to reduce the initial LOS in these patients.…”
Section: Discussionmentioning
confidence: 99%